Justice in transition: CGIAR Climate Security launches climate justice research at INAET 2025? - Pacillo, Grazia; Mastrorillo, Marina; Scartozzi, Cesare (2025)
From energy geopolitics to climate equity, this year’s International Network on African Energy Transition (INAET) conference delivered a powerful convergence of ideas, perspectives, and momentum. Held in Nairobi, the gathering brought together policymakers, private sector leaders, researchers, and development partners to explore how Africa can shape the energy transition on its own terms.